Implementation of Legal Presumption Principle for Notary Deed Makes Partij According to Law No. 2 of 2014 on the Amendment of Act No. 30 of 2004 Concerning Notary Position - Najmi Amudy; Sujatmika Sujatmika; Achmad Sulchan (Jurnal Akta, 2019)
The purpose of this study was to: 1) To identify and analyze the implementation of the principle of presumption valid for notaries who make Partij deed according to Law No. 2 of 2014 concerning amendments to the law No. 30 of 2004 concerning Notary. 2) To identify and analyze problems and solutions for the implementation of a legitimate presumption that a deed Partij Notary according to Law No. 2 of 2014 concerning amendments to the law No. 30 of 2004 concerning Notary. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by normative.Based on the results of data analysis concluded that: 1) an assessment of the Deed as the product of a public official, it must be done with the presumption of unauthorized or Vermoeden van rechtmatigheid or Presumptio lustae Causa, the Deed must be considered valid until there are those who claim deed is invalid then in the contested through the courts and there is a court decision that has permanent legal force 2) in the implementation of the principle of presumption valid for notaries who make Partij deed still major obstacles in the face by the Notary Public. Such constraints due to actions undertaken by the giving false information to the Notary in the process is an authentic deed, causing loss to the parties who feel aggrieved. The solution of the presumption of lawful implementation for notaries who make Partij deed is the absence of legal protection and legal justice for notaries who here become victims of false information given by to the Notary. In the event of the above, none of the violations committed by the Notary. Because of the early events at the root of the problem are the bad faith of the Notary. So that the implementation of their legitimate presumption that a deed Partij Notary shall apply. Because of the early events at the root of the problem are the bad faith of the Notary. So that the implementation of their legitimate presumption that a deed Partij Notary shall apply. Because of the early events at the root of the problem are the bad faith of the Applicant. So that the implementation of their legitimate presumption that a deed Partij Notary shall apply.Keywords: Principle of Legal Presumption, Notary, Partij deed.